Spreading the wealth: a step by step guide to the Swedish socialist model; what it is, what it does, and why America desperately needs it - Signore, Joseph Ronald (Revista de Investigações Constitucionais, 2017)
The goal of the paper is to learn what democratic socialism is and to discuss the history of the Swedish Social Democratic Party (SAP), what their model is, and how it works. Despite the fears Americans have of socialism, Sweden is home to some of the happiest people in the world. This must mean the fears that Americans have of socialism are unfounded. The Swedish people benefit from a wide range of socialist programs – programs which, if instituted in America, would be very popular. Once a thorough understanding of democratic socialism has been achieved, this paper illustrate examples of its use in America. It explore the various ways America has already benefited from democratic socialism and how Americans can move away from capitalism and towards a model such as this. In the end, two points become clear; one, that democratic socialism works, and two, that democratic socialism has been an American ideal all along.